Effect of Ag-doping on crystal structure and high temperature thermoelectric properties of c-axis oriented Ca3Co4O9 thin films by pulsed laser deposition - Sun, T. (2012)
Ag-doped Ca3Co4O9 thin films with nominal composition of Ca3−xAgxCo4O9 (x = 0∼0.4) have been prepared on sapphire (0 0 0 1) substrates by pulsed laser deposition (PLD). Structural characterizations and surface chemical states analysis have shown that Ag substitution for Ca in the thin films can be achieved with doping amount of x ≤ 0.15; while x > 0.15, excessive Ag was found as isolated and metallic species, resulting in composite structure. Based on the perfect c-axis orientation of the thin films, Ag-doping has been found to facilitate a remarkable decrease in the in-plane electrical resistivity. However, if doped beyond the substitution limit, excessive Ag was observed to severely reduce the Seebeck coefficient. Through carrier concentration adjustment by Ag-substitution, power factor of the Ag-Ca3Co4O9 thin films could reach